MY SAY: Let the truth be told - Abd Razak, Dzulkifli (2010)
People around the world were treated to a virtually unprecedented media explosion when some 250,000 classified US documents, including secret diplomatic papers, were released online once again by WikiLeaks.This was despite various warnings, in particular by some Western governments, not to do so.